Contrasting seasonal patterns and factors regulating biocrust N2-fixation in two Florida agroecosystems - Sorochkina, Kira; Strauss, Sarah L.; Inglett, Patrick W. (Frontiers in Microbiology, 2022)
Biocrusts are communities of microorganisms within the top centimeter of soil, often dominated by phototrophic dinitrogen-fixing (N2-fixing) organisms. They are common globally in arid ecosystems and have recently been identified in agroecosystems. However, unlike natural ecosystem biocrusts, agroecosystem biocrusts receive regular fertilizer and irrigation inputs. These inputs could influence seasonal biocrust N2-fixation and their relationship with soil nutrients in perennial agroecosystems, which is of particular interest given crop management requirements. In this study, biocrust and adjacent bare soil N2-fixation activity was measured in the field during the summer, fall, spring, and winter seasons in a Florida citrus orchard and vineyard using both acetylene reduction assays and 15N2 incubations. Samples were analyzed for microbial and extractable carbon (MBC, EC), nitrogen (MBN, EN), and phosphorus (MBP, EP). In both agroecosystems, biocrusts had greater microbial biomass and extractable nutrients compared to bare soil. The citrus and grape biocrusts were both actively fixing N2, despite crop fertilization, with rates similar to those found in natural arid and mesic systems, from 0.1 to 142 nmol of C2H4 g–1 of biocrust dry weight h–1 (equivalent to 1–401 μmol m–2h–1). Lower soil temperatures and higher EC:EN ratios were associated with higher N2-fixation rates in citrus biocrusts, while higher soil moisture and higher EP were associated with higher N2-fixation rates in grape biocrusts. The N2-fixation activity of these agroecosystem biocrusts indicates the possibility of biocrusts to enhance N cycling in perennial agroecosystems, with potential benefits for crop production.